Keanekaragaman Jenis Pohon di Hutan Kota Putroe Phang, Banda Aceh - Tharifah Nia Basri; Irvianty Irvianty; Zuriana Siregar; Suwarno Suwarno; Cut Nanda Defira (Universitas Syiah Kuala, 2025)
Putroe Phang City Forest is one of the green open spaces in the Banda Aceh City area. City forests play a role in improving and maintaining microclimate, aesthetic value, absorbing water, maintaining environmental balance and harmony, and supporting biodiversity. The existence of trees in city forests can improve environmental quality. These efforts can be realized well if the city forest has a high diversity of tree species. This study aims to analyze the diversity of tree species in the Potroe Phang City Forest. Data collection was carried out using the census method by observing all plants with tree habits found in the research location. The parameters observed were the type of tree and the number of individuals from each tree. Data analysis was carried out by calculating diversity using the Shannon-Wienner diversity index equation. The results of the study obtained 31 species from 16 families with a total of 263 individuals. The family with the most species obtained was the Fabaceae family with five species, namely Laucaena leucocephala, Pithecellobium dulce, Pterocarpus indicus, Samanea saman, and Tamarindus indica. This species is a species that has been used as a protective plant. While the highest species obtained is Mimusops elengi or tanjung flower from the Sapotaceae family with a total of 82 individuals. The value of the tree diversity index obtained is 2.609 which is included in the moderate category.